2022
DOI: 10.1007/s11154-022-09721-0
|View full text |Cite
|
Sign up to set email alerts
|

Acromegaly and male sexual health

Abstract: Acromegaly is a rare pathology characterized by chronic hypersecretion of Growth Hormone (GH) and Insulin-like Growth Factor-1 (IGF-1) that causes somatic, metabolic, and systemic changes. The somatotropic axis acts physiologically favoring gonadal function, but when GH is produced in excess it has deleterious effects on many aspects of male sexuality. It is widely demonstrated, in fact, that acromegaly induces hypogonadism through different mechanisms, both through direct mass effect on gonadotropic cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Interestingly, GH levels at diagnosis and IGF-I levels at evaluation and disease control status have been found not to significantly impact sexual function. A strong link between GH and IGF-I excess and sexual dysfunction in men has been extensively elucidated (21,(57)(58)(59)(60)(61)(62). The co-existence of hypogonadotropic hypogonadism due to tumour mass effect or treatments for acromegaly, such as neurosurgery and/or radiotherapy, and high levels of GH and IGF-I has been reported to alter the regular pulsatility of the gonadotropin secretion at the hypothalamic-pituitary level (57), thus contributing to the pathogenesis of erectile dysfunction as the expression of worse sexual health (21,(58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, GH levels at diagnosis and IGF-I levels at evaluation and disease control status have been found not to significantly impact sexual function. A strong link between GH and IGF-I excess and sexual dysfunction in men has been extensively elucidated (21,(57)(58)(59)(60)(61)(62). The co-existence of hypogonadotropic hypogonadism due to tumour mass effect or treatments for acromegaly, such as neurosurgery and/or radiotherapy, and high levels of GH and IGF-I has been reported to alter the regular pulsatility of the gonadotropin secretion at the hypothalamic-pituitary level (57), thus contributing to the pathogenesis of erectile dysfunction as the expression of worse sexual health (21,(58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
“…A strong link between GH and IGF-I excess and sexual dysfunction in men has been extensively elucidated (21,(57)(58)(59)(60)(61)(62). The co-existence of hypogonadotropic hypogonadism due to tumour mass effect or treatments for acromegaly, such as neurosurgery and/or radiotherapy, and high levels of GH and IGF-I has been reported to alter the regular pulsatility of the gonadotropin secretion at the hypothalamic-pituitary level (57), thus contributing to the pathogenesis of erectile dysfunction as the expression of worse sexual health (21,(58)(59)(60). Concomitant cardiovascular, such as arterial hypertension and endothelial dysfunction, respiratory, mainly OSAS, and metabolic complications, including abnormalities in glucose and lipid profile leading to insulin resistance, diabetes mellitus and dyslipidemia, may further compromise erectile function and induce a decrease of desire and arousability in acromegaly (21,58,60).…”
Section: Discussionmentioning
confidence: 99%
“…Hypopituitarism (including central hypogonadism), reported in 10–80% of acromegalic cases, and hyperprolactinemia (affecting more than one third of the patients) are associated with a higher rate of subfertility/infertility in acromegalic patients when compared to a non-acromegalic population of the same age, in both females and males [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Pituitary insufficiency and increased prolactin status are related to larger tumors; 90–95% of pituitary GH secreting tumors are macroadenomas; the additional negative role concerning fertility status is caused by secondary DM [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. For instance, one study from 2022 on 529 acromegalic individuals identified a rate of hyperprolactinemia of 39.1% and a prevalence of hypopituitarism of 34.8%, with the gonadal axis being the most affected pituitary axis; there was a hypogonadism frequency of 29.7% [ 45 ].…”
Section: Sub/infertility Issues In Acromegalymentioning
confidence: 99%
“…In males, the same mechanisms are contributors to erectile dysfunction, while GH growth-promoting effects may be involved in benign prostatic hypertrophy [ 46 , 47 , 48 ].…”
Section: Sub/infertility Issues In Acromegalymentioning
confidence: 99%
“…This intertwined function appears to be characterized by several dynamic redundancies during the transition age, which become evident since puberty, while in adult life, both axes disturbances may impact on reproductive function [ 15 ]. In fact, it is known that, both in peri-pubertal boys and in elderly subjects, exogenous testosterone or GnRH administration is associated with an increase in GH levels [ 16 ]. Likewise, Leydig and Sertoli cells and primary spermatocytes respond to IGF-1, which may also be secreted under gonadotropin control by the Leydig and Sertoli cells themselves [ 16 ].…”
Section: Discussionmentioning
confidence: 99%